Livelihood Transformation Of Farming Communities In Jono Oge Village After The Earthquake And Liquefaction - I Listiqowati; Y Trisyaningsih (LPPM Universitas Tadulako, 2022)
This research aims to describe the transformation process of economy activities of farmers in Jono Oge village post earthquake and liquefaction in 2018. This was a descriptive qualitative research with survey method. The research sample 22 hoseholds selected using purposive sampling technique in five hamlets. The data were obtained through the questionnaire. The research results show that the transformation process of economy activities of the farmers in Jono Oge village to obtain new occupations through middleman as many as 23%, relatives 54%, and neighbors 23%, with initial capital for the middleman family reached from Rp 80,000 to IDR 1,000,000. the duration needed by the famers to do the new occupation is more than twelve months or a year with monthly income average of Rp 700,000 to Rp 7,000,000. The impact of earthquake and liquefaction occurred in 28 September 2018 caused 17 (77%) households had their farm destroyed and 5 (23%) households lost their farm. In addition, people choose to change their livelihood as traders (18%), breeders (27%), labors (27%), and construction labors (27%), with the respondents living place conditions currently are 15 households or 68%, stay in temporary shelter is 4 households or 18%, and stay at emergency home is 3 households or 14%.